Irisin Precursor FNDC5 and Glycemic Control in Patients With Type 2 Diabetes - Lima Mágero, Felipe Rodrigues (J Endocr Soc, 2021)
Introduction: Irisin is a newly discovered myokine whose expression is induced by exercise and PGC1α. Studies have reported its action on adipose tissue cells, leading to their “browning,” and consequent increase in energy expenditure and thermogenesis. In the first description of this hormone, which is a product of cleavage of its precursor (protein 5 containing fibronectin type III domain), elevated irisin levels were associated with improved insulin sensitivity, weight reduction, and better glucose tolerance in animal models. Hence, studies have tried to characterize the role of irisin in glucose regulation, with controversial results. Muscle mass has been a good predictor of irisin circulation in humans and, because it is predominantly synthesized and secreted by skeletal muscle, its use as a potential biomarker of sarcopenia has been investigated. Methods: The aim of this study was to evaluate serum FNDC5 levels according to clinical and metabolic parameters as well as muscle mass from patients with type 2 diabetes (T2DM). Body composition was evaluated by Dual X-ray absortptiometry (DXA) and multifrequency Bioelectric Impedance (BIA) and FNDC5 was measured using an ELISA kit. Results: We evaluated 44 women with type-2 diabetes, mean age of 61.95±8.52 years, mean diabetes duration of 10.25±7.06 years, mean HbA1c of 7.66±1.37, mean fasting plasma glucose of 149.11±38.26 mg/dL, mean BMI of 29.20±5.15 kg/m(2), and mean abdominal circumference of 95.02±12.80 cm. Mean FNDC5/irisin was 18.69±3.67 ng/mL. Although there were no differences in DXA and BIA analyses according to first and top quartiles of serum FNDC5, we identified a negative correlation of serum FNDC5 with fasting plasma glucose (−0.479; P=0.001) and a positive correlation with age (0.422; P=0.004). Conclusion: our data demonstrated that increased serum FNDC5 is related to increased age and poor glycemic control in T2DM. Reference: (1) Perakakis N et al., Physiology and role of irisin in glucose homeostasis. Nat Rev Endocrinol. 2017 (2) Hyun HP et al., The novel myokine irisin:clinical implications and potential role as a biomarker for sarcopenia in postmenopausal women. Endocrine. 2018.